Preferred reporting of case series in surgery; the PROCESS guidelines - Agha, R; Fowler, A; Rajmohan, S; Barai, I; Orgill, D; Process Group (Elsevier, 2016)
Case series have been a long held tradition within the surgical literature and are still frequently published. Reporting guidelines can improve transparency and reporting quality. No guideline exists for reporting case series, and our recent systematic review highlights the fact that key data are being missed from such reports. Our objective was to develop reporting guidelines for surgical case series.A Delphi consensus exercise was conducted to determine items to include in the reporting guideline. Items included those identified from a previous systematic review on case series and those included in the SCARE Guidelines for case reports. The Delphi questionnaire was administered via Google Forms and conducted using standard Delphi methodology. Surgeons and others with expertise in the reporting of case series were invited to participate. In round one, participants voted to define case series and also what elements should be included in them. In round two, participants voted on what items to include in the PROCESS guideline using a nine-point Likert scale to assess agreement as proposed by the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) working group.In round one, there was a 49% (29/59) response rate. Following adjustment of the guideline with incorporation of recommended changes, round two commenced and there was an 81% (48/59) response rate. All but one of the items were approved by the participants and Likert scores 7-9 were awarded by >70% of respondents. The final guideline consists of an eight item checklist.We present the PROCESS Guideline, consisting of an eight item checklist that will improve the reporting quality of surgical case series. We encourage authors, reviewers, editors, journals, publishers and the wider surgical and scholarly community to adopt these.